The role of transient resonances for ultra-fast imaging of single sucrose nanoclusters - Phay J. Ho (Nature Portfolio, 2020)
X-ray free electron lasers provide high photon flux to explore single particle diffraction imaging of biological samples. Here the authors present dynamic electronic structure calculations and benchmark them to single-particle XFEL diffraction data of sucrose clusters to predict optimal single-shot imaging conditions.